Frequency of HCV in Children with Thalassemia Major - Saba Afzal Shaikh, Kiran Fatima, Muhammad Adnan Sadiq, Ibrahim, Fatmah Fahad Alreshidi, Ebtehaj Saud Almughais (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to determine the prevalence of HCV in children presented with thalassemia major. Study Design: Retrospective/Cross-sectional study Place and Duration: Islamic international medical college Riphah university, From March, 2021 to August, 2021 Methods: There were 72 children with ages 3-15 years were presented in this study. Age, gender, and weight were tallied after informed written permission was obtained from each participant. Both the enzyme-linked immunosorbent assay (ELISA) based fast immunochromatographic technique and the chemiluminescence assay utilizing the Abbott method were used in order to test the blood samples of all thalassemia patients for the presence of antibodies against HCV.SPSS 23.0 was used to analyze all data. Results: Among 72 cases, majority of the children were males 40 (55.6%) and 32 (44.4%) cases were females. Mean age of the patients was 11.14+7.49 years and had mean weight 30.6+3.31 kg. Majority of the cases were from urban areas. Frequency of HCV was found among 26 (36.1%) cases in which majority of the cases were males 16 and 10 cases were females. Among 26 cases of HCV positive, blood transfusion, dental procedures and ear piercing was the most common cause found. Conclusion: In this study we concluded that the frequency of HCV among major thalassemia patients were higher found in 36.1% cases and majority were males. Among HCV patients dental procedures and ear piercing among females were the most common causes.